2016
DOI: 10.1007/s11481-016-9716-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulated Antiretrovirals for Penetration of the Central Nervous System: State of the Art

Abstract: The central nervous system is a very challenging HIV-1 sanctuary. But, despite complete suppression of plasmatic viral replication with current antiretroviral therapy, signs of HIV-1 replication can still be found in the cerebrospinal fluid in some patients. The main limitation to achieving HIV-1 eradication from the brain is related to the suboptimal concentrations of antiretrovirals within this site, due to their low permeation across the blood-brain barrier. In recent years, a number of reliable nanotechnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…Data in the literature have been mainly focused on animal infection models of nose-to-brain delivery of ketoconazole in cryptococcal meningoencephalitis [ 7 ] or on adjunctive and long-acting nanoformulated antiretroviral therapies for HIV-associated neurocognitive disorders [ 9 , 45 , 46 ], whereas data regarding bacterial infections are scarce [ 7 ]. NEs described in this study appear suitable to be administered intranasally and indicated potential benefits over other types of delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature have been mainly focused on animal infection models of nose-to-brain delivery of ketoconazole in cryptococcal meningoencephalitis [ 7 ] or on adjunctive and long-acting nanoformulated antiretroviral therapies for HIV-associated neurocognitive disorders [ 9 , 45 , 46 ], whereas data regarding bacterial infections are scarce [ 7 ]. NEs described in this study appear suitable to be administered intranasally and indicated potential benefits over other types of delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while entry and integrase inhibitors are able to reach the CNS, the nucleoside/nucleotide reverse transcriptase inhibitors and non-nucleoside reverse-transcriptase inhibitors can only partially cross the BBB. Conversely, the majority of protease inhibitors (PI) are characterized by a medium/low permeability to the BBB [8,111,112,113]. Moreover, several cellular transporters (P-gp, MRP4, and MRP5) can reduce the optimal intracellular concentration of antiretroviral drugs, thus favoring both the emergence of drug-resistant viruses but also their productive infection to other cells [49,58,114,115].…”
Section: Antiretroviral Therapy and Handmentioning
confidence: 99%
“…In recent years, different types of nanoparticles have been identified. The most important are: (i) Lipid Nanoparticles (liposomes and solid lipid nanoparticles), that easily cross the barrier due to their lipidic nature [116,117]; (ii) Polymeric Nanoparticles, that exploit the interaction with low density lipoproteins (LDL) receptors on the surface of endothelial cells [111,118]; (iii) Inorganic Nanoparticles, such as small size silica with the addition of polyethylene glycol (PEG) [119], and Gold nanoparticles conjugated with cell-penetrating peptides (CPP) [120]. …”
Section: Antiretroviral Therapy and Handmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of nanoengineering has given rise to a new avenue of HIV treatment and prevention research. Nanoparticles are being assessed as vehicles for antiviral drugs to improve drug tolerability, circulation half‐life, and efficacy and as carriers for delivery to the central nervous system ( 14 19 ). They are also being evaluated for the delivery of small interfering RNAs (siRNAs) to silence gene expression in CD4 + T cells, macrophages, and dendritic cells, as well as HIV itself (reviewed in reference 20 ).…”
Section: Introductionmentioning
confidence: 99%